Corporate America and Politics: A Comparative Analysis of the Career Aspirations and Experiences of African Americans - Glenn A. Palmer; Dionne Rosser-Mims (Adult Education Research Conference, 2012)
This paper compares the career development experiences of African Americans in the areas of politics and corporate America. The authors identified congruencies in the career development experiences of African Americans in both career fields to fill the void in the literature concerning empirical research on the career development of African Americans in various disciplines. The researchers‘ findings inform their proposed culturally relevant career development model. Keywords: Career Development, African Americans, Politics, Human Resources, Leadership Development.
Keywords: Career Development; African Americans; Politics; Human Resources; Leadership Development